An-Naqd Al-Adabi Al-‘Arabi Al-Hadis: Naqd An-Nasr ‘Inda Ahmad Asy-Syayib - Budi, Rahmat Dinni Haerul; Tasnimah, Tatik Mariyatut; Husnaya, Ni'ma Royyin (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Literary criticism is a field of study that focuses on efforts to understand and analyze, interpret and assess the merits and demerits of a literary work. The development of modern Arabic literary criticism tends to be difficult to find in Indonesian language literature. Technological advances and influence from the western world are the main factors triggering progress in modern literary criticism. In this way, the author intends to contribute to the development of literature related to Arabic literary criticism, which in particular looks at modern Arabic literary criticism from the perspective of Ahmad Asy-Syāyib. This research explains the implications of Ahmad Asy-Syāyib in developing modern Arabic literary criticism, the concepts and approaches offered. This research uses a qualitative approach with a library research method, the author uses listening and notetaking techniques, by reading relevant references and then describing the results of the data that has been found. This research finds factors in the prosperity of modern Arabic literary criticism, trends in Arabic literary criticism from the classical to the modern era, the concept of literary criticism in general, and Ahmad Asy-Syāyib's approach in criticizing Modern Arabic literature.